Use of species-specific DNA probes for detection and identification of trypanosome infection in tsetse flies - Kukla, B.A.; Majiwa, Phelix A.O.; Young, J.R.; Moloo, S.K.; Ole-MoiYoi, O.K. (Cambridge University Press, 1987)
Species- and subspecies-specific trypanosome DNA hybridization probes have been employed in the detection and identification of trypanosome infections inGlossina morsitans centralis.Several ways of sample preparation including the use of tsetse organ suspensions, proboscides and dissected midguts, as well as tsetse abdominal content touch-blots were explored. The results of hybridization of radio-isotope-labelled species-specific DNA probes to tsetse samples indicated that it was possible to detect trypanosomes in the organs where parasite development is known to characteristically occur for each subgenus. Duplicate slot-blots of samples prepared from midguts of tsetse infected with 2 strains ofT. congolenseand from non-infected fly controls show that it is not only possible to detect infection in tsetse but also to identify the strain of parasite present in a sample after hybridization with the DNA probes specific for each strain. The results, obtained after hybridization of sequential abdominal touch-blots from the same fly with the DNA probe specific for one strain ofT. congolense,indicated that at least 8 positive signals can be observed after an overnight exposure. Because of their simplicity and potentially low cost, the techniques described here would be appealing for screening large numbers of tsetse samples from the field for the presence of any trypanosome residing in the guts or proboscis of the vector. In addition, the possibility of doing multiple touch-blots from the same fly gives the opportunity of detecting mixed trypanosome infections in the vector.